Control in family businesses (2019)
Family businesses are organizations of enormous complexity that have recently become an object of study of disciplines like Management, Sociology, Psychology and Anthropology. These center their attention on the succession, their governing forms, management styles and organizational culture, among others. However, the control is an essential topic to be included in the debate because of its relation with the perpetuity of this kind of organizations. This article aims to reflect first on how companies adopt formal results-oriented control mechanisms and, the important role that the family plays in the development of informal kind of control that integrates a system of shared values and beliefs.